Sistem Pendukung Keputusan Pegawai Terbaik pada Sekretariat Daerah Kota Sibolga dengan Menggunakan Metode Ahp - Daniel Peris Halomoan Hutajulu; Bosker Sinaga (Jurnal Media Informatika, 2021)
The Development Administration Section of the Sibolga City Regional Secretariat will provide good service, which is greatly influenced by the quality of human resources, which in this case are employees who work in the Development Administration Section. The selection of the best employees is carried out not only by direct appointment by the Head of the Section, but must evaluate the criteria that have been carried out by an employee within a certain period of time. To optimize the selection of the best employees, a decision-making system is needed that can help make a decision to determine the selection of the best employee quickly, precisely and reduce errors in determining the best employee with the AHP method (Analytic Hierarchy Process). To make a decision-making system for selecting the best employees at the Regional Secretariat of Sibolga City using the Analytical Hierarchy Process (AHP) method by identifying all system requirements, the next step is the AHP calculation process, namely by making a pairwise comparison matrix that describes the relative contribution or influence of each element on each each criterion.